e-Government information systems interoperability in developing countries: the case of Jordan - Sulehat, Naser Ahmad (Center for Sustainabality Research & Consultancy, 2016)
Objective: This study examines the factors that influence information system (IS) interoperability of e-Government focusing on IS Interoperability as the key concept to reach successful e-Government implementation in Jordan.Methodology: Use of qualitative methods of inquiry has been made to explore study variables and their relationships. A variety of published literatures related to scope of the study has been reviewed along with analyzing the e-Government strategy in Jordan during period 2014-2016.The interoperability levels of e-Government IS have been discussed in this paper. Finally, significant barriers that affect IS interoperability have been identified along with the factors that can drive it successful implementation.Findings: Technical, semantic, and organizational interoperability are main stages for successful e-Government IS interoperability.Information and Communication Technology (ICT) infrastructure, top management support, human resources, data and information, security and privacy, and business process have been found as the major obstacles.Whereas, high level interoperability goals, commitment of government bodies, and customer focus have been identified as main success factors that lead to e-Government IS interoperability.The study suggests that strategies and work process should be aligned, common standards and knowledge should be shared to move towards e-transformation in Jordan. Implications: This study can be starting point for the real life practical solutions for successful implementation of e-Government conceptual frame work.Finding of the study can be used to generalize about the factors that lead to success of IS interoperability within government agencies in other developing countries.This study enriches existing literature in this context.On practical side, the study contributes by identifying IS interoperability success factors and barriers within government agencies.The proposed conceptual model is first stage in the process of understanding factors that influence e-Government IS interoperability.Further studies may be needed to empirically evaluate the proposed conceptual model.